Factors Influencing Financial Reporting Integrity Moderated by Audit Quality - Wati, Yenny; Inrawan, Ady; Kesuma, Indrawati Mara; Yusrizal, Yusrizal; Putri, Debi Eka (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
This research aims to determine the influence of good corporate governance and intellectual capital on the financial reports' integrity. Audit quality is utilized as a moderating variable. The IDX is the secondary data source for the years 2019–2023, and the research sample consists of manufacturing enterprises. WarpPLS, which applies the Partial Least Squares (PLS) data analysis techniques, was used to conduct this research. The influence of good corporate governance and intellectual capital on the financial reports' integrity can be moderated by audit quality. The findings of this study will assist firms in identifying internal and external issues that may affect the integrity of financial reports. Current issues raised in the literature regarding the integrity of financial statements can help in evaluating financial information. Keywords: Integrity of Financial Reports; Institutional Ownership; Independent Commissioner; Intellectual Capital; Audit Quality